Synthesis and properties of cadmium oxide thin films: a review - Ho, Soon Min (International Journal of current advanced research, 2016)
Cadmium oxide thin films are important materials for applications in various photoelectric, solar cell, optoelectronic and other kinds on devices. There are several physical or chemical synthetic methods have been used to prepare transparent CdO films as described by many researchers. The X-ray diffraction study has confirmed the formation of CdO with nano-size scale. CdO films are n-type semiconductors and possess a direct band gap of 2.25 to 2.72eV as shown in optical property studies.